Environmental science : - Miller, George Tyler (Brooks Cole / Thomson Learning, 2004)
This ninth edition places increased emphasis on science-based approaches that interact with political solutions to address environmental problems, offers greater integration of economic and environmental topics, and stresses the shift from large centralized sources of power to a dispersed array of smaller micropower plants. There are two new chapters on community ecology and geology, and expanded coverage of aquatic biodiversity. Tyler is president of Earth Education and Research, and professor of human ecology at St. Andrews Presbyterian College.